2020
DOI: 10.3390/met10101319
|View full text |Cite
|
Sign up to set email alerts
|

The Anisotropic Stress-Induced Diffusion and Trapping of Nitrogen in Austenitic Stainless Steel during Nitriding

Abstract: Plasma nitriding of austenitic stainless steels at moderate temperatures is considered in the presented work. The anisotropic aspects of stress-induced diffusion and influence of nitrogen traps are investigated by kinetic modeling based on rate equations. The model involves diffusion of nitrogen in the presence of internal stress gradients induced by penetrating nitrogen as the next driving force of diffusion after the concentration gradient. The diffusion equation takes into account the fact that nitrogen ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Coarse carbides are formed in the carbide-lacking area. A previous study reported that FCC materials have various carbon (and nitrogen) diffusion reactions depending on the crystal orientation, such as the (111) and (100) planes [ 25 , 26 ]. Comparing the two types of surfaces, because the activation energy of the dense (111) surface is larger than that of the more open (100) surface, it is relatively difficult to cause the reactions by carbon diffusion on the dense (111) surface [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Coarse carbides are formed in the carbide-lacking area. A previous study reported that FCC materials have various carbon (and nitrogen) diffusion reactions depending on the crystal orientation, such as the (111) and (100) planes [ 25 , 26 ]. Comparing the two types of surfaces, because the activation energy of the dense (111) surface is larger than that of the more open (100) surface, it is relatively difficult to cause the reactions by carbon diffusion on the dense (111) surface [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the γ N phase has a mixture of lattice parameters, as this phase is formed with different stoichiometries. The grains might contain crystalline structures with different lattice parameters, as the nitriding process is dependent on the crystalline orientation [40,41]. The broadening of the XRD peaks is caused by the strains induced in the crystal lattice due to the introduction of nitrogen in the solid solution, while the peaks overlapping correspond to the various non-stoichiometric Fe-N concentrations in the austenite CFC structure [14,27,42].…”
Section: Samplementioning
confidence: 99%
“…Cr atoms are hypothesized to have a "trapping effect" on N atoms in the octahedral sites nearby, causing short-range ordering, while additional N atoms can be "detrapped" and diffuse rapidly through the expanded austenite layer [166][167][168]. A further phenomenon, which may influence the diffusion of interstitial atoms, is the high compressive residual stresses which are produced in the modified layer as a consequence of the expansion of austenite lattice, and may become an additional component of the driving force for the interstitial atoms transport [169][170][171].…”
Section: Formation Of Expanded Austenitementioning
confidence: 99%